Placenta Accreta Spectrum: Epidemiology, Risk Determinants, and Clinical Consequences in Benghazi Medical Centre -2022. - H. Getlawi , Omaima; M. Muttardi , Maisa; B. Salih, Asmaa (Benghazi University Medical Journal, 2025)
Abstract Background: Placenta Accreta Spectrum (PAS) is a pregnancy-related disorder characterized by the abnormal adherence of trophoblastic tissue to the uterine myometrium, posing a significant risk of maternal mortality. Key risk factors for PAS include placenta previa and prior cesarean deliveries, which have been rising in frequency. Aim: to explore the risk factors of PAS, incidence, clinical outcomes of affected patients, and strategies to minimize maternal morbidity and mortality. Method: prospective cohort study conducted on 60 patients during the year 2022 in Benghazi Medical Centre including all patients labeled as PAS cases, Review of records for all patients using the structured data collection sheet. The total number of deliveries, caesarean deliveries, maternal and perinatal deaths had been registered; patients were followed up till delivery. Results: Mean age of the studied group was 35.37±5.70, 43.3 % of them were multipara , 56.7% with previous cesarean section three or more times, 71.7% of the studied group with grade III placenta previa, 95.0% experienced some complication, after multivariate analysis C.S 3 times and more is considered risk factor for hysterectomy (p value = 0.03) ( OR 6.12, 95% CI (1.15-32.59), there was statistical significant association between CS delivery and length of hospital stay (p value =0.005). Conclusion: Incidence of placenta accreta increases with advanced age, with multipara and with 3 times and more CS. Placenta previa was coexisting factor in 95% of the cases. Keywords: ,, ,